Inovasi Kurikulum untuk Pendidikan Abad 21: Tinjauan Literatur - Rina Wijayanti; Rizkiyahnur Nasution, Wilda; Satria, Erwinsyah (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
Curriculum innovation is a crucial aspect in preparing young people to face the demands of the 21st century world, which is characterised by rapid technological progress and globalisation. The study of this research uses a literature method, where literature is taken according to related references to identify various curriculum innovations that can improve students' competence in critical thinking, collaboration, creativity, and communication. The results showed that the integration of technology literacy, character education, and project-based learning are key elements in the modern curriculum. The successful implementation of these innovations depends heavily on the readiness of educators, continuous training, and support from educational institutions and the community. Comprehensive policy support and adequate resources are also needed to create an education system that is adaptive and responsive to global change. This study provides insights into strategies and best practices in curriculum design that are relevant and effective for the 21st century, with a focus on developing the skills needed for the future.